2014
DOI: 10.1007/978-3-319-04981-6_15
|View full text |Cite
|
Sign up to set email alerts
|

SAH-Induced MMP Activation and K V Current Suppression is Mediated Via Both ROS-Dependent and ROS-Independent Mechanisms

Abstract: Summary Voltage-gated potassium (KV) channels regulate cerebral artery tone and have been implicated in subarachnoid hemorrhage (SAH)-induced pathologies. Here, we examined whether matrix metalloprotease (MMP) activation contributes to SAH-induced KV current suppression and cerebral artery constriction via activation of epidermal growth factor receptors (EGFRs). Using patch clamp electrophysiology, we observed that KV currents were selectively decreased in cerebral artery myocytes isolated from SAH model rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The gel was stained with Coomassie Brilliant Blue. MMP activity was detected as unstained bands against the background of bluestained gelatin (36).…”
Section: Gelatin Zymographymentioning
confidence: 99%
See 1 more Smart Citation
“…The gel was stained with Coomassie Brilliant Blue. MMP activity was detected as unstained bands against the background of bluestained gelatin (36).…”
Section: Gelatin Zymographymentioning
confidence: 99%
“…After vacuum freezedrying and coating with gold, cells were photo graphed using a scanning electron microscope (JEOL6000). At 12,24,36,48,60, and 72 hours after transfection, cell culture medium was removed and 100 l of methylthiazolyldiphenyltetrazolium bromide (MTT) (1 mg/ml) was added to each well of a 96well plate. Afterward, the cells were incubated for 5 hours at 37°C in 5% CO 2 .…”
Section: Scanning Electron Microscopementioning
confidence: 99%
“…Given the role of K + efflux through K V channels in opposing pressure‐induced membrane depolarization and vasoconstriction, the prediction is that increased (CADASIL) or decreased (SAH) K V channel numbers would alter the degree of negative feedback control, resulting in hyperpolarization (CADASIL) or depolarization (SAH) of PA SMCs. Consistent with this prediction, experimentally measured V m was hyperpolarized (−45 mV) and depolarized (−28 mV) in pressurized (40 mm Hg) PAs obtained from CADASIL mice and SAH model animals, respectively, compared to CTL groups (−35 mV).…”
Section: Impact Of Pathological Increases (Cadasil) or Decreases (Sahmentioning
confidence: 99%
“…90,164,165 Experiments using oxyhemoglobin to mimic the effect of the subarachnoid blood provide solid corroborating evidence. [166][167][168] The precise channels affected, however, are less clear: K v 1.5, K v 2.1 and K v 2.2 transcripts and protein levels are reduced in SAH, 169 although functional measures suggest that K v 2 and K v 7 family members are the pertinent functional targets. 164,170 The involvement of BK channels is contradictory: Koide and co-workers showed that SAH causes a distinct reduction in calcium sparkinduced transient BK currents, 92 while Jahromi and co-workers found that virtually all BK channel characteristics are unaffected in SAH.…”
Section: Endothelial Dysfunction In Subarachnoid Hemorrhagementioning
confidence: 99%